(untitled) (American Journal of Pedagogical and Educational Research, 2026)
The purpose of this paper is to examine the methodological foundations of teaching English sports terminology to students who are majoring in sports. In this article, the theoretical and methodological foundations of the 3D language methodology (Discover–Develop–Demonstrate) in the teaching of sports terminology are highlighted. Additionally, a system of exercises that is based on the integration of Discovery Learning, constructivist, and competency-based approaches, as well as the principles of Performance-Based Assessment and Project Presentation, has been developed. The technique that has been developed is designed to facilitate the gradual mastering of terminological units, the active use of these units in professional communication, and the development of students’ terminological and communicative competence among students. It is possible to use the findings of the study as a scientific and methodological foundation for enhancing the methodology of teaching English to students who are professionally orientated in the field of sports and for raising the efficiency of teaching sports terminology.